Correspondencia entre valoración nutricional mediante antropometría y test Krece Plus en adolescentes de 9-11 años de la Unidad Educativa María Auxiliadora de Cariamanga. - Cumbicus Torres, Ana del Cisne (2016)
The main overall objective of this study was to assess the degree of correspondence between nutritional assessment by anthropometry and the Krece Plus Test in adolescents aged 9-11 years old from the “Maria Auxiliadora” Educational Unit in the city of Cariamanga during the period of July 2015 to September 2016. The study was observational, analytical and cross-sectional. The study population comprised 143 children and adolescents aged 9 to 11 years old. The anthropometric measurements of weight and height were taken following standardized protocols, then the body mass index (BMI) was calculated in order to properly classify the study subjects according to their nutritional status. The nutritional risk and the level of physical activity were evaluated using the Krece Plus screening test. The frequency of normal weight estimated by the BMI was 74.8%, while malnutrition was 25.2% with a prevalence of being overweight and having obesity. About half the participants presented a medium or low nutritional status with 46.8% and 42.7% respectively, while one out of four participants presented a poor level of physical activity according to the Krece Plus test. The results of the Krece Plus test presented no obvious relation to the weight status assessed by the BMI in the study sample. For the analysis and interpretation of data, the statistical program SPSS version 22.0 was used with which the database and relevant calculations were developed. Microsoft Excel was used to create the charts. The quantitative variables: weight for age; height for age; and BMI for age were transformed into qualitative variables according to their Z scores. To summarize the results of these variables, tables of relative frequency expressed as percentages were used. Keywords: Nutritional Risk, Krece Plus Test, Adolescents.